The Beginning of Translation in Pashto Literature - Tareen, Muhammad Naseem; Seemab, Naseeb ullah (sourcecoder, 2024)
In the development of literature where there are many factors, the role of translation is also prominent. In the development of Pashto literature, the process of translation is also very important. From the beginning of Pashto literature to the present time, the translation has shown great excellence in all the periods that have passed. In this research paper, an attempt has been made to briefly review the role of translation in the development of Pashto literature. Especially in this research we discuss about the beginning of Translation in Pashto literature.